Evaluation of a Spanish version of the Buss and Perry aggression questionnaire: Some personal and situational factors related to the aggression scores of young subjects - Santisteban, Carmen; Alvarado, Jesús M.; Recio, Patricia (Personality and individual differences, 2007)
The psychometric properties of a Spanish translation of the Buss and Perry aggression questionnaire adapted for pre-adolescents and adolescents have been studied. A maximum-likelihood confirmatory factor analysis corroborates Buss and Perry’s four-factor structure. The internal consistency of each factor and of the total score has proved to be satisfactory. The four factors are more closely interrelated in pre-adolescents than in adolescents. A second aim of this work has been to further our understanding of the possible relationship between aggression scores and certain outside-school activities of the subjects studied. Two thousand two hundred and eight students filled in the questionnaire together with a self-report concerning their habits. The results show that the aggression scores rise concomitantly with time spent watching television and playing video games and decrease the greater the time devoted to extra-curricular reading or moderate amounts of homework. Statistically significant differences relating to age and gender were also found.